La reparación : una aproximación a su historia, presente y prospectivas. (2017)
This paper develops a study of the concept of reparation of damage from the point of view of the doctrine through the method of documentary analysis. In this order of ideas, from the various meanings of this notion, it is sought to demonstrate that it is necessary to know in what sense the term reparation has been used to understand its scope in the specific context. At the same time, a definition that approximates the current requirements is proposed. It is concluded that the form and scope of application in which it has been used will determine its scope, especially for the judicial operator to whom the right applies who applies law.